Lack of Adipocytes Alters Hematopoiesis in Lipodystrophic Mice - Wilson, Anne; Fu, He; Schiffrin, Mariano; Winkler, Carine; Koufany, Meriem; Jouzeau, Jean-Yves; Bonnet, Nicolas; Gilardi, Federica; Renevey, François; Luther, Sanjiv A.; Moulin, David; Desvergne, Béatrice (Frontiers in Immunology, 2018)
Adult hematopoiesis takes place in the perivascular zone of the bone cavity, where endothelial cells, mesenchymal stromal/stem cells and their derivatives such as osteoblasts are key components of bone marrow (BM) niches. Defining the contribution of BM adipocytes to the hematopoietic stem cell niche remains controversial. While an excess of medullar adiposity is generally considered deleterious for hematopoiesis, an active role for adipocytes in shaping the niche has also been proposed. We thus investigated the consequences of total adipocyte deletion, including in the BM niche, on adult hematopoiesis using mice carrying a constitutive deletion of the gene coding for the nuclear receptor peroxisome proliferator-activated receptor-γ (PPARγ). We show that PpargΔ/Δ lipodystrophic mice exhibit severe extramedullary hematopoiesis (EMH), which we found to be non-cell autonomous, as it is reproduced when wild-type donor BM cells are transferred into PpargΔ/Δ recipients. This phenotype is not due to a specific alteration linked to Pparg deletion, such as chronic inflammation, since it is also found in AZIPtg/+ mice, another lipodystrophic mouse model with normal PPARγ expression, that display only very moderate levels of inflammation. In both models, the lack of adipocytes alters subpopulations of both myeloid and lymphoid cells. The CXCL12/CXCR4 axis in the BM is also dysregulated in an adipocyte deprived environment supporting the hypothesis that adipocytes are required for normal hematopoietic stem cell mobilization or retention. Altogether, these data suggest an important role for adipocytes, and possibly for the molecular interactions they provide within the BM, in maintaining the appropriate microenvironment for hematopoietic homeostasis.